Urgensi Pengawasan Preventif terhadap Qanun No. 3 Tahun 2013 tentang Bendera dan Lambang Aceh - Melisa Fitria Dini (Jurnal Hukum IUS QUIA IUSTUM, 2014)
This research discusses: first, the authority of government evaluation on Qanunof Aceh flag and symbol, and second, the urgency of preventive inspection to Qanun No. 3 of 2013. The method used in this study was normative juridical using regulations of law and conceptual approaches.The result of research shows that: first, the government is not authorized anymore to cancel Qanunof Aceh flag and symbol since the discussion period is outdated as stated in Article 145 of Law No. 32 of 2004 on the Regional Government. Second, the urgency of preventive inspection to Qanun No. 3 of 2014 on Aceh flag and symbol by the government is necessary to guarantee the legal supremacy and to maintain the unity of the Republic of Indonesia.